GAMBARAN TEKANAN DARAH DAN SKALA NYERI MENSTRUASI HARI PERTAMA PADA MAHASISWI DIII KEPERAWATAN UNIVERSITAS SAMAWA - LAILY WIDYA ASTUTI (NHM PRESS, 2022)
Menstruation is the discharge of blood from the uterus caused by the shedding of the endometrium. Complaints that women often feel during menstruation are pain and dizziness. This study is a descriptive with a cross sectional design, the purpose of this study was to determine blood pressure and the scale of menstruation pain on the first day of female students. Respondents in this study were 43 students of DIII nursing, Samawa University and used total sampling technique. The results showed that the blood pressure of students on the first day of menstruation was in the normal category 34 respondents (79.1%) and the hypotension category 9 respondents (20.9%), the most menstruation pain scale on the first day was in the moderate category 34 respondents (79.1%), mild pain category 5 respondents (11.6%) and severe pain controlled category 4 respondents (9.3%). The conclusion in this study are blood pressure of students on the first day of menstruation is in the normal category and the pain scale felt is in the moderate pain category. It is expected that women in the menstrual phase to pay attention to their health condition.